The Relationship Between Sleep Duration And Obesity Among Medical Students at The Faculty of Medicine, University of Muslim Indonesia, Class of 2021 - Darmawan, Inchi Muh Arrayyan; Rijal, Syamsu; Muchtar, Amrizal; Nurmadilla, Nesyana; Ismail, Muhammad Wirasto (Fakultas Kedokteran, Universitas Palangka Raya, 2025)
Obesity is a growing health problem worldwide, including in Indonesia. One factor associated with obesity is inadequate sleep duration. This study aims to determine the relationship between sleep duration and obesity among medical students at the Faculty of Medicine, University of Muslim Indonesia, class of 2021. An analytical cross-sectional design was used. The study sample consisted of 45 students with inclusion criteria of having a BMI > 25 kg/m² and experiencing sleep duration disorders. Data were collected using a questionnaire and analyzed using the Chi-Square test and Cramer's V test. The results showed that the majority of students had adequate sleep duration (53.3%) and were more frequently classified in the Obesity II category (77.8%). The Chi-Square test revealed a significant association between sleep duration and obesity category. The Cramer's V test indicated a moderate correlation between sleep duration and obesity. There is a significant relationship between sleep duration and obesity in students of the Faculty of Medicine, Muslim University of Indonesia, class of 2021